Contesti di crescita e sviluppo della persona: l’interdisciplinarietà come orizzonte pedagogico attuale - Bastianoni, Paola (Studi sulla Formazione/Open Journal of Education, 2022)
Interdisciplinarity is a new challenge in pedagogical epistemic knowledge that increasingly guides dialogue with other knowledge and theoretical approaches. In this article we are going to discuss what is the close interdependence and bidirectionality between human development and context in the light of an integrated reflection between pedagogical and psychological knowledge that increasingly know how to dialogue in the tension to an integrated and competent knowledge in the reading of complexity.